1999
DOI: 10.1046/j.1365-2818.1999.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic calculations of intensity distributions in elemental maps using contrast transfer functions

Abstract: The interpretation of highly resolved elemental maps is not straightforward: one has to consider the quantum mechanical nature of the scattering process as well as the influence of the microscope. Existing calculations of the contrast in elemental maps are based on a non-relativistic approach, while in most of the currently installed electron microscopes, the electrons penetrate the specimen with relativistic energies >/= 200 keV. Therefore, we have recalculated the intensity distribution in elemental maps bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…The calculations show marked differences between relativistic and nonrelativistic results. Similar effects have been demonstrated by Knippelmeyer [10] and Dwyer [11] in simulations of images, where the relativistic calculation exhibits strong deviations from nonrelativistic results even at voltages of 80 or 100 kV.…”
Section: Introductionsupporting
confidence: 79%
“…The calculations show marked differences between relativistic and nonrelativistic results. Similar effects have been demonstrated by Knippelmeyer [10] and Dwyer [11] in simulations of images, where the relativistic calculation exhibits strong deviations from nonrelativistic results even at voltages of 80 or 100 kV.…”
Section: Introductionsupporting
confidence: 79%
“…8). As the measured signal in a transmission electron microscope is not only influenced by the specimen, but also by the instrumental parameters, the corresponding transfer functions have been included in the calculation [40]. The main instrumental effects are the aberration of the lens system and the modulation transfer of the CCD camera.…”
Section: Microstructural Characterization By Transmission Electron MImentioning
confidence: 99%
“…We note in passing that Knippelmeyer and Kohl [27] have shown that relativistic corrections can make a significant difference to the form of calculated elemental maps. For the current parameters -low energy loss and moderate (effective) aperture size -we can tolerably neglect these corrections, and the calculations presented here assume the non-relativistic model for the inelastic transition.…”
mentioning
confidence: 84%
“…Nevertheless, it has been established that direct interpretation of EFTEM images is not always possible, making simulation a necessary adjunct to experiment [26][27][28][29]. Previous simulation work has focused on making the complex calculations as timeefficient as possible.…”
Section: Article In Pressmentioning
confidence: 99%